A Voronovskaya-type theorem for a certain nonlinear Bernstein operators - KARSLI, Harun; ATIN, Huseyin Erhan (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
The present paper concerns with the nonlinear Bernstein operators NBnf of the form ... acting on bounded functions on an interval [0; 1]; where Pn;k satisfy some suitable assumptions. As a continuation of the very recent paper of the authors [11], we estimate the rate of convergence by modulus of continuity and provide a Voronovskaya-type formula for these operators. We note that our results are strict extensions of the classical ones, namely, the results dealing with the linear Bernstein polynomials. Mathematics Subject Classification (2010): 41A35, 41A25, 47G10.